GEOMETRY AND TOPOLOGY OF EXTERNAL AND SYMMETRIC PRODUCTS OF VARIETIES - Laurentiu George Maxim (Tạp chí Khoa học Đại học Đà Lạt)
We give a brief overview of recent developments on the calculation of generating series for invariants of external products of suitable coefficients (e.g., constructible or coherent sheaves, or mixed Hodge modules) on complex quasi-projective varieties.